Analisis Pengaruh Tingkat Pengangguran, Output Gap, dan Upah Minimum Provinsi terhadap Inflasi di 33 Provinsi di Indonesia pada Tahun 2014-2018 - Yosua Siagian; Banatul Hayati (Diponegoro Journal of Economics, 2020)
The Phillips Curve Theory shows the trade-off relationship between inflation and unemployment. This study aims to analyze what factors influencing the inflation rate in the economy of 33 provinces in Indonesia in the period of 2014-2018. The data used in this research include open unemployment rate, output gap, and provincial minimum wage as the independent variables, along with inflation as the dependent variable. The sample of this study includes 33 provinces in Indonesia in the period of 2014-2018. The data used are secondary data obtained from Statistics Indonesia and Bank Indonesia, with random effect as its analytical method. The result of this study indicates that the inflation rate in 33 provinces in Indonesia in the period of 2014-2018 is influenced by the level of unemployment, it show inflation caused demand full inflation. In Addition UMP increase caused cost push inflation. Meanwhile, the output gap has no effect on inflation in 33 provinces in Indonesia in the same period.